PENILAIAN RISIKO PEKERJAAN PERGUDANGAN PADA PT BORNEO MITRA BERSAMA DI BALIKPAPAN - Siboro, Impol; Liku, James Evert Adolf; Zain, Abdul; Sondakh, Laura Kartarina (Program Studi Kesehatan dan Keselamatan Kerja, 2022)
Warehousing or warehouse is a very important part to support the smooth operation of the upstream oil and gas industry. Work accident is one of the risks that can cause operational disruptions in the warehouse and can cause delays in the process of supplying and delivering tools and materials needed for oil and gas production activities. More than 145,000 people work in 7,000 warehouses, where the fatal injury rate for warehousing is higher than the average for all industries (OSHA, 2004). Therefore companies are required to have a system that regulates hazard identification, risk assessment and risk control or commonly known as Hazard Identification, Risk Assessment and Risk Control (HIRARC). Currently, PT Borneo Mitra Bersama currently has a project at PT Pertamina Hulu Mahakam, namely the Warehouse Support Project. Based on PT BMB's preliminary observations there has been no HIRARC implementation related to the project's operational activities, while the project has a high risk value based on the tender documents. In this study using a qualitative approach. The study design in the research used was based on the ISO 31000: 2018 standard with a semi-quantitative risk analysis technique, by taking informants using a purposive sampling technique, totaling 6 people. The research results show that the risk assessment in PT Borneo Mitra Bersama's warehousing operations has 33 risks identified with the results of the risk evaluation level obtained at the initial risk, namely 6 (18.18%) risk priority level 3, 34 (72.72%) substantial level risk and 11 (33.33%) very high level risk, while the risk evaluation results obtained for residual risk are 24 (9.09%) acceptable level risk and 9 (27.27%) priority 3 or tolerable level risk risk.